P829 Cardiac uptake level in 99mTc-DPD scintigraphy in ATTR amyloidosis: is there any association with the prognosis?. (17th January 2020) - Almeida, I; Victor, M; Cruz, I; Marques, A; Gomes, C; Pereira, H
Abstract: Introduction: The uptake of bone-seeking radiotracers in 99mTc-DPD scintigraphy has been shown to be highly sensitive for cardiac transthyretin (ATTR) amyloid. Progressive levels of cardiac involvement are associated with poor prognosis. Purpose: Evaluation of the prognostic impact of the tracer uptake level in the heart through 99mTc-DPD scintigraphy. Methods: Single center retrospective analysis of patients' data referred to perform a 99mTc-DPD between September 2014- July 2018 due to an abnormal echocardiogram or family history of ATTR. Data was collected regarding clinical, echocardiographic and 99mTc-DPD parameters to evaluate prognostic impact of the uptake level on cardiovascular events, namely hospitalizations due to acute heart failure, myocardial infarction or stroke, and all-cause mortality. Results: 35 patients were reviewed of whom 12 (34.3%) had a positive 99mTc-DPD, performing the diagnosis of an ATTR amyloidosis: mean age 78.4 ± 7.3 years, 100% male. 33.3% had a cardiac uptake level 2 (group 1) and 66.6% level 3 (group 2). Group 1 patients were younger (mean age 72.3 ± 4.6 versus 81.5 ± 6.5 years, p 0.03). At the time of diagnosis, most patients in both groups were in NYHA class II. Mean value of NTproBNP in group 1 patients was 4322.4 ± 35.0 versus 6387.7 ± 60.0 pg/ml (p 0.03); troponin level was not statistically different between groups (88.3 ± 63.1 versus 54.5 ± 16.1 pg/ml, p 0.228). On transthoracic echocardiogram evaluation, there were no significant differences between groups regarding cardiac function: mean ejection fraction 48.8 ± 6.3 versus 43.9 ± 11.5% (p 0.453) and mean global longitudinal strain -10.4 ± 2.8 versus -9.0 ± 2.9% (p 0.531). Although almost patients presented a nearly normal ejection fraction, almost have diastolic dysfunction (75 versus 100%, p 0.140) and pericardial effusion (100% in both groups). Hypertrophy level was similar between groups: septum thickness was 19.5 ± 0.7 in group 1 and 19 ± 1.4mm in group 2 (p 0.386). During follow-up, 25% of group 1 patients were hospitalized due to acute heart failure and 25% died. In group 2 patients, there were 25% of hospitalizations due to heart failure and all-cause mortality rate of 50%. Conclusions: In our population, there was no significant association between the cardiac uptake level in 99mTc-DPD scintigraphy and cardiac symptoms or cardiac function evaluated through transthoracic echocardiogram at the time of diagnosis. However, higher levels of cardiac uptake were associated with higher mortality in the follow-up period. This data suggests that 99mTc-DPD scintigraphy should be performed not only for diagnosis but also for prognosis assessment in these patients.